Efficacy and safety of surufatinib plus toripalimab in treatment-naive, PD-L1-positive, advanced or metastatic non-small-cell lung cancer and previously treated small-cell lung cancer: an open-label, single-arm, multicenter, multi-cohort phase II trial - Ying Cheng; Panpan Zhang; Ming Lu; Zhendong Chen; Lijie Song; Si Shi; Feng Ye; Xing Zhang; Baorui Liu; Dongmei Ji; Yanqiao Zhang; Weiguo Su; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Combining the programmed death-1 inhibitor toripalimab and the angio-immuno kinase inhibitor surufatinib showed preliminary antitumor activity in patients with advanced solid tumors in a phase I study. Here, we report the efficacy and safety of this combination regimen in treatment-naive advanced or metastatic non-small-cell lung cancer (NSCLC) patients with a programmed death-ligand 1 (PD-L1) tumor proportion score (TPS) of 1% or greater (PD-L1-positive) and patients with previously treated small-cell lung cancer (SCLC). Methods This open-label, single-arm phase II study included patients with treatment-naive advanced or metastatic PD-L1-positive NSCLC or previously treated SCLC in China. Patients received surufatinib (250 mg orally, once daily) plus toripalimab (240 mg intravenously, once every 3 weeks). Primary endpoint was investigator-assessed objective response rate (ORR) per RECIST v1.1. Secondary endpoints included duration of response (DoR), disease control rate, progression-free survival (PFS), overall survival (OS), and safety. Results Forty-three patients were treated (NSCLC cohort, n = 23; SCLC cohort, n = 20). ORRs (95% CIs) were 57.1% (34.0–78.2) in the NSCLC cohort and 15.8% (3.4–39.6) in the SCLC cohort. Median duration of response was not reached (NR) in both cohorts. Median PFS was 9.6 (5.5–NR) and 3.0 months (2.8–4.1), respectively, and median OS was 24.3 (10.8–NR) and 11.0 months (5.0–15.7), respectively. Grade ≥ 3 treatment-related adverse events were reported in 24 patients (55.8%) overall. Conclusion Surufatinib plus toripalimab showed encouraging antitumor activity and a tolerable safety profile in patients with treatment-naive advanced or metastatic PD-L1-positive NSCLC and previously treated SCLC.